The Koskobilo (Olazti, Navarre, Northern Iberian Peninsula) paleontological collection: New insights for the Middle and Late Pleistocene in Western Pyrenees. (20th November 2020) - Gómez-Olivencia, Asier; Arlegi, Mikel; Arceredillo, Diego; Delson, Eric; Sanchis, Alfred; Núñez-Lahuerta, Carmen; Fernández-García, Mónica; de Alvarado, Mónica Villalba; Galán, Julia; Pablos, Adrián; Rodríguez-Hidalgo, Antonio; López-Horgue, Mikel A.; et al.
Abstract: The destroyed site(s) of Koskobilo (Olazti, Navarre, Northern Iberian Peninsula) have yielded unique archaeo-paleontological evidence in the Western Pyrenees region. The quarry uncovered a karstic site with faunal remains in 1940, and fossils were recovered both in situ and from the quarry dump. Ten years later, while the quarry was still working, a new visit to the dump yielded a large lithic assemblage and additional fossil remains with a different taphonomic pattern, which has been interpreted as the remains coming from a different site or zone within the same karst system. Here we re-study the paleontological evidence and provide new dating on a speleothem covering a Stephanorhinus hemitoechus tooth, which has yielded a minimum date of c. 220 ka for part of the assemblage. In total, the fossil assemblage comprises 38 mammal and six avian taxa and three fish remains. The faunal evidence indicates that in 1940 a mix of taxa from both the Middle and Upper Pleistocene were recovered, and it is difficult to assign most of them to a concrete period. However, based on biochronological criteria some of the identified taxa (e.g., Ursus thibetanus, Ursus cf. deningeri, Cuon cf. priscus, Macaca sylvanus, cf. Megaceroides ) could be roughly contemporaneous with the dated rhino tooth, which would provide a new window to the Middle Pleistocene of the region, with deposits from MIS 7d and/or older. Despite the difficulties in studying this collection, recovered without stratigraphic context and in a salvage operation, Koskobilo has yielded an important paleontological assemblage which helps to understand the paleoecology of the Middle Pleistocene human occupations in the Western Pyrenees.